Sistem Penjadwalan Perkuliahan Multi-Level Berbasis Cloud dengan Validasi Real-time dan Notifikasi WhatsApp untuk Transparansi Beban Akademik - Dony Kusuma Hadi; Hudan Studiawan; Hadziq Fabroyir (Pusat Publikasi Ilmiah LPPM Institut Teknologi Sepuluh Nopember, 2026)
Traditional lecture scheduling systems are often inefficient, prone to conflicts, and lack transparency in teaching workload distribution. This study has developed a cloud-based automated timetabling system that integrates Google Workspace and WhatsApp to address the complexities of multi-level (undergraduate, master’s, and doctoral) course scheduling in higher education environments. The system combines constraint-based validation with a heuristic algorithm to enable real-time conflict detection and transparent distribution of credit-hour-based teaching loads. Implemented on a real-world dataset of 120 courses (including parallel classes), 11 classrooms, and 26 lecturers, the system successfully generated schedules less than 17 seconds. Real-time validation achieved a response time of 1.2 seconds per edit data in cell, and the automated notification module delivered teaching load summaries to 95% of lecturers via WhatsApp and email. The system improved administrative efficiency compared to manual processes and enhanced the accountability of academic resource management through real-time visibility and user-centric communication